1998
DOI: 10.1161/01.cir.97.18.1773
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Region of the Angiotensin-Converting Enzyme Gene Influences Interindividual Differences in Blood Pressure Levels in Young White Males

Abstract: Background-The renin-angiotensin system regulates blood pressure through its effects on vascular tone, renal hemodynamics, and renal sodium and fluid balance. Methods and Results-Using data from a large population-based sample of 1488 siblings having a mean age of 14.8 years and belonging to the youngest generation of 583 randomly ascertained three-generation pedigrees from Rochester, Minn, we carried out variance components-based linkage analyses to evaluate the contribution of variation in four renin-angiote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
2
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(89 citation statements)
references
References 48 publications
6
77
2
4
Order By: Relevance
“…16,17 Nevertheless, in our population the difference of genotype frequencies between men with highest BP (fifth quintyl) and men with lowest BP (first quintyl) was not significant (P = 0.468) ( Table 2), in agreement with a previous study. 18 We have not found a relationship between genotypes and family history of hypertension or evident clinical hypertension (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…16,17 Nevertheless, in our population the difference of genotype frequencies between men with highest BP (fifth quintyl) and men with lowest BP (first quintyl) was not significant (P = 0.468) ( Table 2), in agreement with a previous study. 18 We have not found a relationship between genotypes and family history of hypertension or evident clinical hypertension (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…Two large population-based studies found only marginally significant evidence of association and linkage, for BP and the I/D dimorphism. 12,16 Plasma ACE levels are remarkably stable within an individual, while marked differences are observed between individuals. 3,4 The results of a combined segregation-linkage analysis in French families suggested that the I/D dimorphism was in strong LD with an unmeasured functional mutation of the ACE gene.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the association of ACE I/D dimorphism and the risk of developing CVDs, such as essential hypertension (EH) [9][10][11][12][13][14][15][16][17][18] and myocardial infarction (MI), [19][20][21][22][23][24][25][26][27][28] have generated inconsistent information. This instigated a search for new polymorphisms in the ACE gene to identify better markers or actual functional variants.…”
Section: Introductionmentioning
confidence: 99%
“…17 Previously, we also reported that serum ACE levels were significantly higher in the DD and ID genotypes than in the II genotype in subjects who underwent cardiac catheterization 15 or renal biopsy 16 in our hospital. Recently, three studies, two in Caucasians 7,8 and one in Japanese, 9 independently reported a significant association between the ACE I/D polymorphism and hypertension in male subjects. The current study confirmed these earlier observations in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several studies reported evidence of a significant relation between the ACE I/ D polymorphism and hypertension in male subjects but not in female subjects. [7][8][9] However, it was also shown that this relation was not consistently seen in male subjects, but was changeable depending on other factors such as age. 10 In addition, recent studies of population-based samples of three differ-ent areas in Japan presented conflicting results regarding the association of the ACE I/D polymorphism and hypertension.…”
Section: Introductionmentioning
confidence: 98%